Assessing water requirements and suitability for apple growth at county scale in China: a phenological modeling approach during key growth stages - Ru, Xiaoya; He, Tianzhi; Yan, Guochao; He, Yong; Zhu, Zhujun; Yu, Qiang; He, Jianqiang (Frontiers in Plant Science, 2025)
Water shortages greatly challenge high-quality apple production in dryland agricultural regions. Bridging the gap between water use and apple crop water requirements, as well as clarifying water suitability levels, are essential steps to improve water use efficiency. This study innovatively introduced phenological models to accurately predict apples’ phenological stages, thus constructing a dynamic crop coefficient (Kc) curve. By skillfully integrating this curve with classic FAO 56 Penman-Monteith (P-M) ETo model, the water requirements (WR) and water suitability (S) were evaluated during apple flowering-fruit setting, fruit expansion, and coloring-maturity stages. The results showed that the average durations of the apple phenological stages were 22 days for flowering-fruit setting, 102 days for fruit expansion, and 39 days for fruit coloring-maturity. Unexpectedly, counterintuitive results emerged regarding water requirements and suitability across the phenophases. Despite the fruit expansion stage having the highest average water requirement (319 mm), multi-year data indicated ‘relatively suitable’ (S=0.8) conditions for most counties. In contrast, although the average water requirement during flowering-fruit setting was 120 mm, the suitability level was classified as ‘unsuitable’ (S=0.3), indicating a water shortage, particularly in Xinjiang, the northwest Loess Plateau, and northern Bohai Bay areas. The coloring-maturation stage, with an average water requirement of 113 mm, was classified as ‘very suitable’ (S=1.5), reflecting highly favorable conditions. As this stage progressed, over-humidity conditions began in the Southwestern Cool Highlands and spread to the southwestern Loess Plateau. These findings revealed that the relationship between water requirements and suitability was not linear and emphasized the critical need for focused water management during the flowering-fruit setting stage to ensure sustainable apple production.